A Conceptual Model on the Relationships between Business Strategy, Business Model Innovation, Resource Configuration and Performance - Avanti Fontana, Siti Yasmina Zubaedah (ITB, 2012)
The main objective of this study is to develop a research to develop sound strategic business model innovation that has practical implication on show to innovate firm's business models. The research indentifes factors attributin to effective business model: business strategies, type of business model innovations and types of resource configurations. This study framwork can guide leaders and managers to acquire the appropriate capability of coping with business model dynamics as well as major transformation that arises from business model innovations. In addition, the study provides insightful contributions in explaining the influence of business strategies (defender, prospector, analyzer) on business model innovations and firm resource configuration, and their influence on business model effectiveness. This study model is valuable considering the limited amount of empirical work previously done on the topic in question. based on a case-study research survey in seven companies in Indonesia that deem further tests. One case (Food Co.) is highlighted for the study to show some presence and absence of alignment between business strategy, business model innovation and resource configuration.